(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Annona crassiflora is a native tree from Brazilian savanna area of the state of Minas Gerais. The ethanolic extract of A. crassiflora wood was obtained and purified, and an annonaceous acetogenins-rich fraction was obtained and characterized. The in vivo antitumor activity and toxicity of this fraction were evaluated in Ehrlich solid tumor-bearing Swiss mice. The annonaceous acetogenins showed a pronounced in vivo antitumor effect, with a reduction in the Ehrlich’s tumor growth of 38% and 20% after single intratumoral and intravenous administration, respectively, at a dose of 1.25 mg/kg, as compared to the control group. Concerning toxicological studies, the absence of clinical signs and renal toxicity could be observed, and all animals survive throughout the entire experimental period (14 days). By contrast, mielotoxicity and hepatotoxicity could be detected in mice treated with the A. crassiflora wood extract.